Full-admission radial turbine for waste heat recovery organic Rankine cycles. (February 2020) - Giovannelli, A.; Archilei, E.M.; Salvini, C.
Abstract: Organic Rankine Cycle (ORC) plants are interesting systems for power production by Waste Heat Recovery (WHR), although their application, especially for small/medium plants, could be not economically convenient. This is due to the inherent low thermodynamic cycle efficiency connected to the temperature of the heat source. Therefore, to avoid further penalizations, plant components (especially the turbine) should reach high performance both at nominal and off-design conditions. The paper deals with the design (from a 1-D to a fully 3-D level) of a full-admission radial-inflow turbine for a WHR ORC plant with a power output less than 50 kW. A parametric study was carried out to improve the turbine performance varying the most relevant geometric parameters, and the most promising geometry was analyzed in off-design conditions.